A lunar dust simulant: CLDS-i. Issue 4 (15th February 2017) - Tang, Hong; Li, Xiongyao; Zhang, Sensen; Wang, Shijie; Liu, Jianzhong; Li, Shijie; Li, Yang; Wu, Yanxue
Highlights: CLDS-i is similar to the real lunar dust. Most of CLDS-i particles surfaces embedded some nanophase α-Fe 0 . CLDS-i can be applied to lunar dust treatment technology and toxicology study. Abstract: Lunar dust can make serious damage to the spacecrafts, space suits, and health of astronauts, which is one of the most important problems faced in lunar exploration. In the case of rare lunar dust sample, CLDS-i with high similarity to the real lunar dust is an important objective for studying dust protection and dust toxicity. The CLDS-i developed by the Institute of Geochemistry Chinese Academy Sciences contains ∼75 vol% glass and a little nanophase metal iron (np-Fe 0 ), and with a median particle size about 500 nm. The CLDS-i particles also have complicated shape and sharp edges. These properties are similar to those of lunar dust, and make the CLDS-i can be applied to many fields such as the scientific researches, the treatment technology and toxicological study of lunar dust.